Evaluation of 24 corn hybrids for silage agronomic performance under both irrigated and dryland conditions - R.N. Sonon; B.S. Dalke; D.L. Holthaus; D.R. Bonilla; L. Pfaff; John E. Boyer; B.E. Brent; K.K. Bolsen; Matthew A. Young (Kansas Agricultural Experiment Station Research Reports, 1993)
In 1992, 24 corn hybrids were grown under both irrigated and dryland conditions and were harvested at 90% of the kernel milk line. Growing condition and hybrid significantly affected plant height and the number of days to the tasseling and silking stages. Most dryland hybrids had higher dry matter (DM) contents than irrigated hybrids, but all 24 hybrids had higher grain yields under irrigation. Growing condition and hybrid also significantly affected whole-plant DM and stover yields and percentages of cob and stover. The grain portion made the greatest contribution to the higher whole-plant silage yields for the irrigated hybrids compared to their dryland counterparts.
Keywords: Cattlemen' s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Corn; Hybrid; Silage; Yield